Therapeutic Potential of Remote Ischemic Conditioning in Vascular Cognitive Impairment - Xu, Rui; He, Qianyan; Wang, Yan; Yang, Yi; Guo, Zhen-Ni (Frontiers in Cellular Neuroscience, 2021)
Vascular cognitive impairment (VCI) is a heterogeneous disease caused by a variety of cerebrovascular diseases. Patients with VCI often present with slower cognitive processing speed and poor executive function, which affects their independence in daily life, thus increasing social burden. Remote ischemic conditioning (RIC) is a noninvasive and efficient intervention that triggers endogenous protective mechanisms to generate neuroprotection. Over the past decades, evidence from basic and clinical research has shown that RIC is promising for the treatment of VCI. To further our understanding of RIC and improve the management of VCI, we summarize the therapeutic potential of RIC on the risk factors and pathobiologies of VCI, which includes reduced risk of recurrent stroke; decreased high blood pressure; improved cerebral blood flow, white matter integrity, and endothelial function; and attenuated oxidative stress and inflammation.